2021
DOI: 10.1101/2021.08.17.456617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct neural circuits establish the same chemosensory behavior in C. elegans

Abstract: Animals frequently exhibit the same behavior under different environmental or physiological conditions. To what extent these behaviors are generated by similar vs. distinct mechanisms is unclear. Moreover, the circumstances under which divergent neural mechanisms establish the same behavior, and the molecular signals that regulate the same behavior across conditions, are poorly understood. We show that in C. elegans, distinct neural mechanisms mediate the same chemosensory behavior at two different life stages… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…One example is CO 2 sensing in different developmental stages. Consistent with a previous report that AIY is not required for CO 2 response in dauers unlike adults [23], we easily identified that the connection from BAG [24], which is responsible for CO 2 detection to AIY does not exist in the dauer connectome while it exists in the adult (Supplementary Data 1). Now, it is possible to focus on additional specific connections and check how the neuronal functions differ in terms of CO 2 sensing using optogenetics and calcium imaging like the IL2-RIG experiments we have conducted.…”
Section: Resource For Comparative Connectomicssupporting
confidence: 91%
“…One example is CO 2 sensing in different developmental stages. Consistent with a previous report that AIY is not required for CO 2 response in dauers unlike adults [23], we easily identified that the connection from BAG [24], which is responsible for CO 2 detection to AIY does not exist in the dauer connectome while it exists in the adult (Supplementary Data 1). Now, it is possible to focus on additional specific connections and check how the neuronal functions differ in terms of CO 2 sensing using optogenetics and calcium imaging like the IL2-RIG experiments we have conducted.…”
Section: Resource For Comparative Connectomicssupporting
confidence: 91%
“…In contrast, S. stercoralis freeliving adults are neutral to CO2 (Figure 1). In addition, C. elegans dauer larvae and S. stercoralis iL3s, which are homologous life stages [54][55][56], show opposite responses to CO2; C. elegans dauers are attracted to CO2 [39,57,58], whereas S. stercoralis iL3s are repelled by CO2 (Figure 1) [25,42]. C. elegans dauers form when environmental conditions are unfavorable, and CO2 attraction likely enables dauers to migrate toward potential food sources [39,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, C. elegans dauer larvae and S. stercoralis iL3s, which are homologous life stages [54][55][56], show opposite responses to CO2; C. elegans dauers are attracted to CO2 [39,57,58], whereas S. stercoralis iL3s are repelled by CO2 (Figure 1) [25,42]. C. elegans dauers form when environmental conditions are unfavorable, and CO2 attraction likely enables dauers to migrate toward potential food sources [39,58,59]. Thus, CO2 preferences of homologous life stages are not conserved across nematode species but instead reflect the ethological requirements of each species and life stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation